2012
DOI: 10.1094/pdis-09-11-0776-re
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Esca of Grapevine: The Development of Foliar Symptoms and Their Association with Xylem Discoloration

Abstract: Lecomte, P., Darrieutort, G., Liminana, J.-M., Comont, G., Muruamendiaraz, A., Legorburu, F.-J., Choueiri, E., Jreijiri, F., El Amil, R., and Fermaud, M. 2012. New insights into esca of grapevine: The development of foliar symptoms and their association with xylem discoloration Plant Dis. 96:924-934.A new study on the development of foliar symptoms of esca was carried out from 2004 to 2006 in five mature vineyards in Aquitaine, France. Symptoms were monitored for severity and changes over time. Initial foliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 16 publications
3
86
0
Order By: Relevance
“…Therefore, we hypothesized that germplasm accessions with resistance to these other grape diseases may have resistance to trunk diseases. This is because Botryosphaeria dieback and Phomopsis dieback are not associated with diagnostic foliar symptoms (4,20,42), and foliar symptoms of Esca have very rarely been reproduced consistently under controlled conditions (22). Additionally, the North American hybrid Fennell 6 (V aestivalis) x Malaga (V. vinifera) DV1T0166, which is resistant to the obligate biotrophic fungus E. necator (9), showed higher susceptibility to E. lata than most V vinifera cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we hypothesized that germplasm accessions with resistance to these other grape diseases may have resistance to trunk diseases. This is because Botryosphaeria dieback and Phomopsis dieback are not associated with diagnostic foliar symptoms (4,20,42), and foliar symptoms of Esca have very rarely been reproduced consistently under controlled conditions (22). Additionally, the North American hybrid Fennell 6 (V aestivalis) x Malaga (V. vinifera) DV1T0166, which is resistant to the obligate biotrophic fungus E. necator (9), showed higher susceptibility to E. lata than most V vinifera cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Grapevine infections by fungal trunk pathogens result consistently in the formation of cankers and discolorations of the wood, but not all trunk pathogens cause diagnostic foliar symptoms. In contrast, grapevines with Botryosphaeria dieback do not develop diagnostic foliar symptoms, but, instead, develop spur dieback, which is a characterisfic of all of the trunk diseases (20,42). aleophilum) (22), is associated with foliar symptoms ranging from a distinct interveinal chlorosis and necrosis of leaves on individual shoots to the total wilting of all leaves on the entire plant (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterised by a brown red discoloration and black streaking in the xylem (considered as ‘young esca’) with the later development of a white rot in the trunk (‘esca proper’). Both young esca and esca proper in the trunk are associated with leaf tiger stripe symptoms as well as symptoms on berries [68]. Plants with heavily damaged trunks may suddenly die due to esca symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In fact research (Mugnai et al, 1999;Bertsch et al, 2013) demonstrated the important role of both nursery (Surico et al, 2004) and vineyard management in the infection and symptom development. For example, training systems and pruning techniques not only create infection courts for pathogens, but also favour dysfunctions in water flow in the vine (Lecomte et al, 2012). Indeed, water flow impairment, interacting primarily, but not exclusively, with pathogen virulence factors (i.e.…”
Section: Grapevine Trunk Diseasesmentioning
confidence: 99%